(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The study was carried out in the fields of Livestock Research Division / Nineveh Research Department, using 756 (ROSS 308) birds, 1 day old, distributed on nine experimental treatments, 3 replicates / treatment, each containing 28 birds, the chicks were fed nine experimental starter and finisher diets depending the age of chicks to determine the effect of substituting Faba Bean Minor substitutes instead of soybeans and Barley soaked water instead of Maize on some broiler productive characteristics.The best results were obtained with a 25% FB minor which have no significant differences to control treatment in BW, WG and FI in most experimental periods, also there are no significant effect to 25% and 50% on (heart, liver, gizzard, pancreas, fat, chest and secondary part) weights and dressing%. BSW 25% had no significant differences with control treatment over experimental period for BW, FI only and for most experimental periods for WG and FCR, BSW 25% and 50% had no significant effect on (heart, liver, gizzard, pancreas, fat, chest and secondary part) weights, there are insignificant effect between control treatment and 25% BSW only in dressing%. We conclude from the present study the possibility of using FB minor as a substitute of soybeans and barley soaked water instead of yellow corn in low concentrations up to 25%.